Non-contact Heart Rate Estimation using High Radio Frequency Radar - Al-Hasanol Gumanti, Sudirman (2022)
Heart rate, respiration rate, core temperature, and blood pressure are the four most important vital indicators. Electrocardiography (ECG) and respiratory inductance plethysmography are examples of the contact methods that are typically utilised in the course of a study of a person's pattern of heartbeat and respiration (RIP). There is an interest in developing contactless vital sign monitors that are more comfortable to use. A measurement method that does not involve contact has a number of advantages, including the following: It does not irritate the skin, create discomfort, or lead to infection in the same way that electrodes and straps do (e.g. in case of patient with severe burns or injures). This is of utmost significance over lengthy periods of time, making the detector an excellent choice for long-term continuous monitoring thanks to its suitability in this regard. The patients are not aware that they are being measured, thus they are less likely to make any changes to their vital signs. This allows for an increase in reliability of the results. Therefore, in order to detect vital signs without having to make direct touch with the skin, a wireless sensor will need to be developed. It is anticipated that this technology will have a wide variety of uses; however, some of the most important commercial applications include security screenings and safety systems for automobiles, as well as medicine and healthcare. At various checkpoints for transportation and passenger safety, such as airports, train stations, and even casinos, there is an interest in the detection of aberrant physiological activity. For instance, the installation of such a device at a point of registration at an airport will supply us with valuable information regarding the subject's real-time heartbeat and breathing rates. If he is anxious or if there is something he wants to conceal from us, we would like to know. In addition, it is of the utmost importance to identify commercial truck drivers who have an irregular heartbeat rate, which may be the result of drug use, an insufficient amount of sleep, or stress. In order to accurately extract vital signs from a remote location using frequency modulation continuous wave (FMCW) radars operating at 60GHz and 77GHz, multiple signal processing techniques have been applied to the data collected by these radars. Methods such as phase-based, parametric estimation, and time-varying window analysis, in conjunction with multiple input multiple output (MIMO) diversity channel combining, were utilised in this study with the goal of accurately detecting the participants' heart rates and respiration rates. In this body of work, a comparison is made between the acquisition times and accuracy of vital sign detection that have previously been achieved in state-ofthe-art microwave radar systems operating at lower frequencies. The results of a single participant's measurements taken at a variety of distances will be reported and compared to the findings of any other relevant contact measurements. Importantly, the capabilities and limitations of applying the techniques to a real-time system will be illustrated with the help of a Texas Instruments mmwave vital sign detection chip. This is because realtime application of the techniques is critical. The diagnosis and monitoring of obstructive sleep apnea syndrome (OSAS is the most common sleep breathing problem) and other respiratory diseases is an obvious market for this technology. OSAS affects roughly 4% of men and 2% of women in Western countries [14].